Liquid-liquid phase separation of nucleocapsid proteins during SARS-CoV-2 and HIV-1 replication - Bao-An Chau; Venessa Chen; Alan W. Cochrane; Leslie J. Parent; Andrew J. Mouland (Cell Reports, 2023)
Summary: The leap of retroviruses and coronaviruses from animal hosts to humans has led to two ongoing pandemics and tens of millions of deaths worldwide. Retrovirus and coronavirus nucleocapsid proteins have been studied extensively as potential drug targets due to their central roles in virus replication, among which is their capacity to bind their respective genomic RNAs for packaging into nascent virions. This review focuses on fundamental studies of these nucleocapsid proteins and how their intrinsic abilities to condense through liquid-liquid phase separation (LLPS) contribute to viral replication. Therapeutic targeting of these condensates and methodological advances are also described to address future questions on how phase separation contributes to viral replication.